Paving the way: Urban Health, Food Systems, and the Imperative for Holistic City-Led Action [version 1; peer review: 1 approved, 2 approved with reservations] - Luz Maria De Regil; Lucy Diekmann; Nevin Cohen; Lukar Thornton; Ana Moragues-Faus; Katrina Lundberg (F1000Research)
Most of the food produced globally is consumed in urban centres, and urban populations rely heavily on purchasing the foods they consume in place of growing, catching, or producing food themselves. Urban populations are thus highly dependent on the types of foods available to them and their relative prices. Rapid urbanization is catalysing changes across the food system and in turn, shaping urban diets. Traditionally viewed as a problem predominantly faced by rural areas, food insecurity and malnutrition (both undernutrition and overweight and obesity) are on the rise in urban areas globally. Likewise, urban environments can foster unsafe food environments, increasing the risk of foodborne illnesses and death. Considering an increasingly urbanized world, this paper describes critical links between food systems and urban health. It identifies housing development, digitalization, labour transitions and dietary transitions as emerging and interrelated trends that are changing the way people access, purchase and consume food in urban areas. This paper proposes potential interventions and tools for holistic, city-led policies and actions that make healthier and safer food more available and affordable for everyone, to inspire and encourage practitioners and policymakers at the city, regional, national and international levels to increase their ambition and act urgently.